Comparison of baroreflex sensitivity determined by cross-spectral analysis at respiratory and 0.1 Hz frequencies in man - Nováková, Zuzana; Šťastná, Jana; Honzíková, Klára; Hrstková, Hana; Honzíková, Nataša; Závodná, Eva; Fišer, Bohumil; Honzík, Petr (Physiological research, 2010)
Non-invasive methods of determination of baroreflex sensitivity (BRS, ms/mmHg) are based on beat-to-beat systolic blood pressure and inter-beat interval recording. Sequential methods and spectral methods at spontaneous breathing include transient superposition of breathing and 0.1 Hz rhythms. Previously, a cross-spectral method of analysis was used, at constant breathing rate using a metronome set at 0.33 Hz, enabling separate determination of BRS at 0.1 Hz (BRS0.1Hz) and respiratory rhythms (BRS0.33Hz). The aim of the present study was to evaluate the role of breathing in the spectral method of BRS determination with respect to age and hypertension. Such information would be important in evaluation of BRS at pathological conditions associated with extremely low BRS levels. Blood pressure was recorded by Finapres (5 minutes, controlled breathing at 0.33 Hz) in 118 healthy young subjects (YS: mean age 21.0±1.3 years), 26 hypertensive patients (HT: mean age 48.6±10.3 years) with 26 age-matched controls (CHT: mean age 46.3±8.6 years). A comparison of BRS0.1Hz and BRS0.33Hz was made. Statistically significant correlations were found between BRS0.1Hz and BRS0.33Hz in all groups: YS: r=0.52, p<0.01, HT: r=0.47, p<0.05, and CHT: r=0.70, p<0.01. The regression equations indicated the existence of a breathing-dependent component unrelated to BRS (YS: BRS0.33Hz=2.63+1.14*BRS0.1Hz; HT: BRS0.33Hz=3.19+0.91*BRS0.1Hz; and CHT: BRS0.33Hz=1.88+ +1.01*BRS0.1Hz; differences between the slopes and the slope of identity line were insignificant). The ratios of BRS0.1Hz to BRS0.33Hz were significantly lower than 1 (p<0.01) in all groups (YS: 0.876±0.419, HT: 0.628±0.278, and CHT: 0.782±0.260). Thus, BRS evaluated at the breathing rate overestimates the real baroreflex sensitivity. This is more pronounced at low values of BRS, which is more important in patients with pathologic low BRS. For diagnostic purposes we recommend the evaluation of BRS at the frequency of 0.1 Hz using metronome-controlled breathing at a frequency that is substantially higher than 0.1 Hz and is not a multiple of 0.1 Hz to eliminate respiratory baroreflexnon- related influence and resonance effect on heart rate fluctuations.
Keywords: financování organizované; dospělí; Baroreflex; hypertenze; Age Factors; Adult; Respiratory Mechanics; mladý dospělý; Predictive Value of Tests; prediktivní hodnota testů; časové faktory; Time Factors; věkové faktory; lidé; mechanika dýchání; krevní tlak; modely kardiovaskulární; srdeční frekvence; Financing, Organized; Middle Aged; Hypertension; Young Adult; Blood Pressure Determination; měření krevního tlaku; lidé středního věku; baroreflex; Models, Cardiovascular; Blood Pressure; Heart Rate; Humans